Surgical treatment of a retropharyngeal abscess in a bull. Issue 1 (29th June 2015) - Williams, Helen J; Townsend, Neil; Rubio Martinez, Luis
Abstract : A 12‐month‐old bull with chronic respiratory stridor and dysphagia was presented. Endoscopic evaluation of the upper airway revealed a large swelling of the dorsal pharynx, partially obstructing the airway. The swelling was investigated further with the bull anaesthetised. A hand was advanced through the mouth to the level of the mass while an endoscope was placed via the nasopharyngeal route to visualise the swelling. Needle aspiration revealed thick purulent material. The wall of the abscess was digitally broken down, and the endoscope was advanced into the cavity of the abscess to allow flushing with normal saline. Immediately following surgery, there was a noticeable reduction in respiratory noise. Two days following surgery, appetite had returned to normal, and by four days following surgery, minimal respiratory noise was present at rest. Four months after being discharged, the owner reported the animal to be completely normal.